2015
DOI: 10.2337/db15-1372
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Cold Acclimation Recruits Brown Adipose Tissue in Obese Humans

Abstract: Recruitment of brown adipose tissue (BAT) has emerged as a potential tool to combat obesity and associated metabolic complications. Short-term cold acclimation has been shown not only to enhance the presence and activity of BAT in lean humans but also to improve the metabolic profile of skeletal muscle to benefit glucose uptake in patients with type 2 diabetes. Here we examined whether short-term cold acclimation also induced such adaptations in 10 metabolically healthy obese male subjects. A 10-day cold accli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
214
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(229 citation statements)
references
References 40 publications
8
214
0
2
Order By: Relevance
“…This is the first study to demonstrate that the average ambient lower temperature, during the 4 and 6 weeks prior to the measurement day, under free-living situations, is associated with an elevation in the BAT-d. Laboratory studies showed that daily cold exposure (10°C to 17°C, 2 to 6h∕day), when dressed in unnaturally light clothing (t-shirt with underwear), for 10 days to 6 weeks, promoted BAT recruitment, 5,[8][9][10] and the results of these previous studies might provide a hint for the consideration of our result. Cohade et al 11 showed a rise in the monthly prevalence of BAT activity during the winter, but the rise was delayed by a few months, in relation to the beginning of a decrease in the AmT.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This is the first study to demonstrate that the average ambient lower temperature, during the 4 and 6 weeks prior to the measurement day, under free-living situations, is associated with an elevation in the BAT-d. Laboratory studies showed that daily cold exposure (10°C to 17°C, 2 to 6h∕day), when dressed in unnaturally light clothing (t-shirt with underwear), for 10 days to 6 weeks, promoted BAT recruitment, 5,[8][9][10] and the results of these previous studies might provide a hint for the consideration of our result. Cohade et al 11 showed a rise in the monthly prevalence of BAT activity during the winter, but the rise was delayed by a few months, in relation to the beginning of a decrease in the AmT.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that human BAT activity is related to cold-induced thermogenesis, 5 body weight, 5 and glucose tolerance. 6,7 Furthermore, daily cold exposure increased the BAT activity in healthy individuals, 5,8,9 obese individuals, 10 and patients with type 2 diabetes. 7 Thus, BAT is expected to be a potential tool to combat obesity and lifestyle-related diseases.…”
mentioning
confidence: 99%
“…Chronic cold conditioning of human subjects also has been shown to increase BAT activity in several recent studies (27,28). These lines of evidence have led some to postulate the energetic consequences of browning the entire WAT depot, including both visceral and subcutaneous fat (29).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in fat tissue also accompany cold stress. In general, BAT increases activity and volume with cold stress [10,[34][35][36][37], and recently it has been recognized that cells in white adipose tissue (WAT) can be converted to a brown phenotype by cold exposure [38] (reviewed by [39]). Smith et al have recently visualized significant differences in BAT in mice at ST and TT showing that the lipid to water ratio in BAT is reduced in colder temperatures in accord with its role in thermogenesis [40].…”
Section: Glossarymentioning
confidence: 99%